2007
DOI: 10.3233/jad-2007-11310
|View full text |Cite
|
Sign up to set email alerts
|

Height and Alzheimer's Disease: Findings from a Case-Control Study

Abstract: Hospitals of Cleveland. On entry to the study, height was measured on 239 probable or possible AD patients and 341 healthy controls living in northeast Ohio. Risk of AD was modeled as a function of quartile of height, APOE genotype, years of education and year of birth. Analyses were stratified by gender. For men, cases were more likely to be shorter when compared to controls (p = 0.001). There was only a small difference in mean height between AD cases and controls among women (p = 0.05). For men, height in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…No relationship between height and cognition was found for females. Supporting our results, several studies have found shorter stature to be associated with higher risk of cognitive compromise (relationship found in males only [4]; relationship found in both males and females [5, 6]), including AD and vascular dementia [79]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No relationship between height and cognition was found for females. Supporting our results, several studies have found shorter stature to be associated with higher risk of cognitive compromise (relationship found in males only [4]; relationship found in both males and females [5, 6]), including AD and vascular dementia [79]. …”
Section: Discussionsupporting
confidence: 90%
“…This may suggest that childhood factors may contribute to this group of neurodegenerative diseases [2]. Adult body height, although affected by genetics [3], is a surrogate for early life illness, stress, and poor nutrition [3], and has been associated with adult cognitive performance [46]; and in some studies, with Alzheimer’s disease (AD) and vascular dementia [79]. Anthropometric measures associated with height, including head circumference, leg length, knee height, and arm span have also been found to be related to adulthood cognition [1519].…”
Section: Introductionmentioning
confidence: 99%
“…A case-control study from the USA found a lower risk of Alzheimer's disease in women, adjusted for age and education, but not men. 35 However, when they stratified by APOE e4 status they found this association only in women without that allele (OR = 0.88, 95% CI 0.80-0.97). A further Korean study found an association, only in women, between leg length and Alzheimer's disease, after adjustment for age, rural residence in childhood and education.…”
Section: Mechanisms Of Effectmentioning
confidence: 95%
“…It indicated that the prevalence of poor cognitive performance declined consistently with increasing height from 25% in men shorter than 154 cm to 9% in those taller than 174 cm [26] . Data from the research registry of the University Memory and Aging Center of Case Western Reserve University and University Hospitals of Cleveland revealed that among men, height in the highest quartile (>179.7 cm) had a 59% lower risk of developing Alzheimer's disease than that in the lowest quartile (<169.5 cm) [27] . The Israeli Ischemic Heart Disease project reported that rates of dementia declined for taller height quartiles (ORs 0.78-0.51) after controlling for age, social economic status, and geographical area of birth in a logistic regression [28] .…”
Section: Discussionmentioning
confidence: 99%